6w+5=-(5w+7)

Simple and best practice solution for 6w+5=-(5w+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6w+5=-(5w+7) equation:


Simplifying
6w + 5 = -1(5w + 7)

Reorder the terms:
5 + 6w = -1(5w + 7)

Reorder the terms:
5 + 6w = -1(7 + 5w)
5 + 6w = (7 * -1 + 5w * -1)
5 + 6w = (-7 + -5w)

Solving
5 + 6w = -7 + -5w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '5w' to each side of the equation.
5 + 6w + 5w = -7 + -5w + 5w

Combine like terms: 6w + 5w = 11w
5 + 11w = -7 + -5w + 5w

Combine like terms: -5w + 5w = 0
5 + 11w = -7 + 0
5 + 11w = -7

Add '-5' to each side of the equation.
5 + -5 + 11w = -7 + -5

Combine like terms: 5 + -5 = 0
0 + 11w = -7 + -5
11w = -7 + -5

Combine like terms: -7 + -5 = -12
11w = -12

Divide each side by '11'.
w = -1.090909091

Simplifying
w = -1.090909091

See similar equations:

| x-12+2x+6=6x+84 | | q-8=-17 | | y^2+8y=0 | | -7x+4=-9x+8 | | -7y+4=-8y+2 | | -7x+4=-9+8 | | x=3x-24 | | t^2-5td-24d^2= | | c^2-2c+36= | | (a^2b^3+7ab^2)+(6ab^2-a^2b^3)= | | 45+3.5X=27.5+-x | | i=(200)(0.13)(2) | | 6+4x+x=46 | | p-26=-42 | | -21.9=7.3t | | 100x-49=0 | | 8(2x+7)=2(8x+9) | | 10x^2-23x+12= | | 16x-5x+280=18x | | 8+4p-5=9p+11-6p | | I=(500)(.12)(2) | | p=2(76)+2(107) | | 12t=88 | | 4m=24 | | -6(2b+4)+(13b-4)=0 | | 3X^2-X^2-1X=-1 | | Y^2-11Y-12= | | 16x-5x+80=18 | | 5r+4r=72 | | -(4y+2)-(3y-4)=-6 | | Y^2-9Y+20= | | p-44=-42 |

Equations solver categories